Discovery zone in the library : a new service for the children - Tan, Florence Kia Mui. (2011)
The National Library Board, Singapore, embarked on a pilot service known as Discovery Zone which aims to provide increased learning moments for children. This research evaluates one of the products from the eyes of the users under the umbrella of Piaget and Vygotsky's theories of cognitive development. The importance of play in a child's development from these theories helps confirm the need to incorporate play and fun in Discovery Zone. The research studied children between the ages of 6 to 10. The findings showed that children were attracted to hands-on activities and challenging games. Children preferred manipulatives only if it added value to the activity. The product was therefore not as important as the process or activity. The study also showed that difficulties faced by the children led them to seek assistance from their friends, parents and staff assigned to Discovery Zone. The concepts of "disequilibrium", "assisted learning", "scaffolding" were drawn into the study. The role of a facilitator to provide the "zone of intervention" raises the need for a library staff specialising in children. The differences in the perception between parents and their children point to the need to value children's feedback who are the best persons in telling designers what is considered fun and play.